Impact of Production Practices on Organoleptic Intensity Scale of Different Rice Cultivars - Amit Kesarwani; Madhu Sharma; Sachin Kumar Vaid; Shih Shiung Chen (Journal of Pharmacy and Nutrition Sciences, 2015)
The purpose of this research was to relate mean organoleptic scores of organically and conventionally grown rice (n = 5) in japonica cultivars (Taikeng No. 16 and Kaohsiung No. 139). The 0-7 organoleptic scale is used in trials to measure the agronomic practices impact on sensory attributes of rice cultivars. However, the precise relationship between farming system and organoleptic analysis of rice remains independent variables. Judges (n = 10) used a common 0-7 scale to report the 6 sensory attributes viz. appearance, aroma, flavor, cohesion, hardness and overall acceptability while keeping cultivar Taikeng No. 9 as control. The scale ranges from – 3 to + 3 as very poor to excellent. The study demonstrates sensory attributes as inherited trait of rice; while no improvement found in cooking and eating quality under seasonal or agronomic variations. Interestingly, the aroma was reported as only better parameter when grown under organic farming compared to conventional farming (– 0.49 and – 0.62 over control, respectively). Also, the positive co-relationship exists between amylose content and organoleptic analysis while antagonistic link to crude protein content. The study cleared that management method, per se, did not influence any flavory attributes and detected no changes by the sensory panel. Further descriptive analysis needed with different conditions such as variety, degree of milling, growing location and moisture content which also played significant role in determining flavor and eating quality of rice cultivars.